2018
DOI: 10.1016/j.acmx.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with peripheral arterial disease in an adult population from Colombia

Abstract: Background: Cardiovascular diseases (CVD) are the most important cause of mortality in Latin America, while peripheral arterial disease (PAD) is the third leading cause of atherosclerotic cardiovascular morbidity. Objective: To establish the prevalence of PA D and the distribution of traditional CVD risk factors in a population from the Department of Cauca, Colombia. Methods: A cross-sectional study was conducted on a total of 10,000 subjects aged ≥40 years, from 36 municipalities. An ankle---brachial index (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
1
10
0
6
Order By: Relevance
“…24,25 Urbano et al have reported that PAD risk is elevated by 4.7 folds when the TG / HDL ratio is above 4. 23 Consistent with these results, in our study, we found that 68.4% of the PAD patients had DL, and the TG / HDL ratio was 4.53±3.64.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…24,25 Urbano et al have reported that PAD risk is elevated by 4.7 folds when the TG / HDL ratio is above 4. 23 Consistent with these results, in our study, we found that 68.4% of the PAD patients had DL, and the TG / HDL ratio was 4.53±3.64.…”
Section: Discussionsupporting
confidence: 90%
“…15 In some studies, the prevalence of PAD was similar in men and women. 22,23 In our study, this rate was higher in male population, and the exact reason of this is currently unknown.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…La causa común es la aterosclerosis 2 . La EAP, después del infarto agudo de miocardio y el accidente cerebrovascular, es la tercera causa principal de morbilidad y mortalidad cardiovascular aterosclerótica en todo el mundo 3 . En 2010, los cálculos sugirieron que > 200 millones de personas en todo el mundo vivían con EAP.…”
Section: Introductionunclassified